Day to day and night after night: Temporal NPN constructions in Present Day English - Sommerer, Lotte (English Noun Phrases from a Functional-Cognitive Perspective: Current Issues, 2022)
This paper analyzes temporal symmetric NPN constructions in which both nouns are singular, identical, and conjoined by a preposition (e.g. day to day, hour upon hour, night after night). The constructions’ binominal structure, their idiomatic nature, their apparent frozenness, and their syntactic restrictions (e.g. determiners are not permitted) make them an interesting target for linguistic analysis. Although several researchers have analyzed these constructions in different frameworks (e.g. Travis 2001; Matsuyama 2004; Haïk 2009; Jackendoff 2008, 2013; Zwarts 2013; Kim & Sells 2015), there is no study which looks at these constructions quantitatively. Consequently, the paper analyzes data from the Corpus of Contemporary American English. The constructions’ frequency and productivity, as well as their syntactic function and extension potential is being investigated (e.g. day after day of suffering, hour by precious hour). Additionally, the constructions’ semantics and interesting clustering and multiplication patterns are discussed. In terms of theoretical modeling, the paper takes a Usage-based Cognitive Construction Grammar approach (Goldberg 2003, 2006, 2019; Tomasello 2003; Hilpert 2014; Diessel 2015, 2019; Ellis et al. 2016; Sommerer & Smirnova 2020) and sketches the constructional network of [CNsg,timei P CNsg,timei]Cx –constructions.<br